Estereotipos de género y su influencia en el bullying escolar a estudiantes LGBTIQ+ de la Carrera de Trabajo Social de la Universidad Nacional de Loja: Un estudio de casos múltiples desde la perspectiva socio-crítica - Paredes Riofrio, Nathaly Mishell (2024)
Socioculturally ingrained gender stereotypes create rigid expectations regarding gender roles, thereby intensifying violence and discrimination in various domains, including education. In this context, experiences of bullying or harassment against LGBTIQ+ students often arise based on gender. The primary objective of this research was to study gender stereotypes and their influence on school bullying experienced by LGBTIQ+ students enrolled in the Social Work program at the National University of Loja. The methodological strategy employed a mixed qualitative and quantitative approach, characterized by its flexibility, continuous evaluation, and adaptation to the study's circumstances. This descriptive research adopted a multiple case 3 study design, utilizing techniques such as in-depth interviews and surveys. The study population consisted of a convenience sample of 10 LGBTIQ+ students, selected using the snowball sampling technique. The results were triangulated with previous related research, allowing the determination that gender stereotypes significantly influence the bullying experiences of LGBTIQ+ students. These experiences are rooted in sociocultural heteronormative patterns, leading to social exclusion and manifestations of violence through bullying or harassment in family, educational, and, to a lesser extent, workplace settings. The study concluded that expressions of stereotypes and bullying are evident in the use of derogatory labels, the imposition of gender-based roles, and social prejudices regarding masculinity and femininity. In the educational domain, bullying experiences were most prevalent during secondary education, with transgender women being the most affected by psychological and physical violence as well as social exclusion.